Aspect ratio compression effects on metals and polymers - Khan, A S; Balzer, J E; Wilgeroth, J M; Proud, W G (Journal of physics. Conference series, 2014)
Previous research has studied the effects of altering the shape and size of samples over a range of compression rates. Several discrepancies exist in the published data, probably due to the wide range of techniques used. The research here was carried out to bridge this gap. Cylindrical polycarbonate and aluminium (6082) samples, with varying aspect ratios, were subject to a range of strain rates between 10-4 − 102 s−1, with further data gained for polycarbonate at higher strain rates between 102 − 103 s−1, and the stress-strain relationships obtained, compared and discussed.